All That Light Up Are Not Sarcoidosis – The Great Masquerader: A Case of LMNA Cardiomyopathy - Cillis, Nicole I.; Park, Carolyn J.; Amjad, Aysha; Sundaravel, Swethika H. (British Journal of Healthcare and Medical Research, 2024)
Lamin A/C (LMNA) cardiomyopathy is a rare cause of non-ischemic dilated cardiomyopathy (DCM), caused by a gene mutation in Lamin A/C. It manifests with electrical abnormalities before the onset of heart failure, much like cardiac sarcoidosis (CS). Both have similar imaging findings. Detailed family history and genetic testing are crucial in making the correct diagnosis.